Пошаговое объяснение:
1)
10целых 5/8 - х = 7целых 3/5
х = 10целых 5/8 - 7целых 3/5
х = 10целых 25/40 - 7целых 24/40
х = 3целых 1/40
2)
(х - 2целых 7/8) + 3целых 5/6 = 4целых 2/3
х - 2целых 7/8 = 4целых 2/3 - 3целых 5/6
х - 2целых 7/8 = 4целых 4/6 - 3целых 5/6
х - 2целых 7/8 = 3целых 10/6 - 3целых 5/6
х - 2целых 7/8 = 5/6
х = 5/6 + 2целых 7/8
х = 20/24 + 2целых 21/24
х = 2целых 41/24
х = 3целых 17/24
3)
4/5 - ( х + 1/60 ) = 2/3
х - 1/60 = 4/5 - 2/3
х - 1/60 = 12/15 - 10/15
х - 1/60 = 2/15
х = 2/15 + 1/60
х = 8/60 + 1/60
х = 9/60
х = 3/20
1)6:7/9=6/1:7/9=6/1×9/7=6×9/1×7=54/7=7 5/7;
2)13:26/29=13/1:26/29=13/1×29/26=13×29/1×26=377/26=14 13/26=14 1/2;
3)9/16:6=9/16:6/1=9/16×1/6=9×1/16×6=9/96=3/32;
4)2 10/13:3 3/26=36/13:81/26=36/13×26/81=36×26/13×81=936/1.053=8/9;
Вроде правильно.